2020
DOI: 10.1177/1526602820923044
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Endovascular Aortic Repair With Left Subclavian Artery Coverage Is Associated With a High 30-Day Stroke Incidence With or Without Concomitant Revascularization

Abstract: Purpose: To evaluate the perioperative stroke incidence following thoracic endovascular aortic repair (TEVAR) with differing left subclavian artery (LSA) coverage and revascularization approaches in a real-world setting of a nationwide clinical registry. Materials and Methods: The National Surgical Quality Improvement Program registry was interrogated from 2005 to 2017 to identify all nonemergent TEVAR and/or open LSA revascularization procedures. In this time frame, 2346 TEVAR cases met the selection criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…7 Varkevisser et al confirmed this as well: of the 33 TEVAR patients experiencing a perioperative stroke 8 (24%) died within 30 days. 18 One patient (2%) died in-hospital and 8 during median follow-up of 3 years, and none of the LSA revascularizations in our series required reintervention during follow-up. We report an overall survival rate of 94% and 83% and primary assisted patency rate of 98% after one and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…7 Varkevisser et al confirmed this as well: of the 33 TEVAR patients experiencing a perioperative stroke 8 (24%) died within 30 days. 18 One patient (2%) died in-hospital and 8 during median follow-up of 3 years, and none of the LSA revascularizations in our series required reintervention during follow-up. We report an overall survival rate of 94% and 83% and primary assisted patency rate of 98% after one and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…17 Similarly, Varkevisser et al confirmed a higher risk for stroke of 5.2% in patients undergoing TEVAR with LSA coverage vs. 2.3% without LSA coverage, but found a higher stroke incidence when the LSA was concomitantly revascularized 7.5% vs. 4.4% without concomitant LSA revascularization. 18 Konstantinou et al recommended a staged approach, first with LSA revascularization and then TEVAR, after finding significantly higher 30-day mortality and stroke rate in single stage procedures. 14 All strokes in our group occurred after concomitant LSA revascularization during TEVAR, 3 of them in an emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite lack of common consensus for proximal landing at ascending aorta, clinicians have gradually explored the safety and feasibility of this practice with promising outcomes. 2,1517 Kuo et al used handmade fenestrated stent-grafts to preserve all supra-aortic branches in TEVAR for 13 patients with zone 0 landing. Over a mean follow-up of 20 months, no aortic-related mortality and complication resulting from proximal landing zone and fenestration occurred, and secondary endovascular procedures were performed on 6 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Stroke following TEVAR with LSA coverage frequently occurs in the real-world setting, and concurrent LSA revascularization is not associated with a lower stroke incidence. [20] Hypogastric hypoperfusion due to visceral atherosclerosis may be eliminated by collateral circulation from the subclavian artery. The LSA closure in these cases may cause stroke and spinal ischemia.…”
Section: Discussionmentioning
confidence: 99%